1981
DOI: 10.1093/ajcn/34.8.1617
|View full text |Cite
|
Sign up to set email alerts
|

The “metabolically-obese,” normal-weight individual

Abstract: A great many disorders including maturity-onset (type II) diabetes, hypertension, and hypertriglyceridemia are frequently associated with adult-onset obesity and improve with caloric restriction. It is the premise of this brief review that there are patients with these disorders who are not obese according to standard weight tables or other readily-available criteria; but who would also respond favorably to caloric restriction. It is proposed that such individuals might be characterized by hyperinsulinism and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
305
0
9

Year Published

1989
1989
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 489 publications
(322 citation statements)
references
References 28 publications
8
305
0
9
Order By: Relevance
“…33 This review concluded that 'even modest amounts of physical activity can have tremendous health benefits in high-risk youngsters (for example, obese, high blood pressure)'. 33 The 'fat-but-fit' phenotype Classical and recent studies in adults, [69][70][71] as well as in children and adolescents, 18,50,51 have shown the strong relationship between PA and adiposity, expressed both as BMI or percent body fat. In light of this, we can state that PA influences the MS risk within fatness categories.…”
Section: Physical Activity As a Therapeutic Tool In Pediatrics P Brammentioning
confidence: 99%
“…33 This review concluded that 'even modest amounts of physical activity can have tremendous health benefits in high-risk youngsters (for example, obese, high blood pressure)'. 33 The 'fat-but-fit' phenotype Classical and recent studies in adults, [69][70][71] as well as in children and adolescents, 18,50,51 have shown the strong relationship between PA and adiposity, expressed both as BMI or percent body fat. In light of this, we can state that PA influences the MS risk within fatness categories.…”
Section: Physical Activity As a Therapeutic Tool In Pediatrics P Brammentioning
confidence: 99%
“…It may be hypothesized that, although the discrepant group did not show central obesity, they have metabolic abnormalities associated with these unfavorable lifestyles and that these may lead to the consequences of metabolic syndrome. Ruderman et al 28,29 insisted that metabolically obese, normal-weight individuals are also predisposed to type 2 diabetes, hypertriglyceridemia, and coronary heart disease like people with overt obesity; therefore, it is important to identify and treat these individuals before these diseases become overt. Insulin resistance can occur independently of obesity and apparently contributes to a high prevalence of type 2 diabetes and CVD.…”
Section: Ncep-r(+) and Idf(+) Ncep-r(+) And Idf(à) Ncep-r(à) And Idf(à) Ncementioning
confidence: 99%
“…This relationship was also observed in non-obese men. Our non-obese male subjects included metabolically obese subjects who had accumulated visceral fat despite having normal BMI; 15,16 this may explain the signi®-cant relationship observed in non-obese men. Further studies must be carried out to clarify the mechanism by which circulating concentrations of a-MSH are increased in obese male subjects.…”
Section: Plasma Levels Of a A-msh In Obese Menmentioning
confidence: 99%